Cover Image. (5th September 2019) - Soares‐Bezerra, Rômulo José; da Silva Ferreira, Natiele Carla; de Almeida Alves, Tânia Maria; Zani, Carlos Leomar; Rosa, Luiz Henrique; Faria, Robson Xavier; da Silva Frutuoso, Válber; Alves, Luiz Anastacio
Abstract : The cover image is based on the RESEARCH ARTICLE A new insight into purinergic pharmacology: Three fungal species as natural P2X7R antagonists by Rômulo José Soares‐Bezerra et al., https://doi.org/10.1002/ptr.6412 .